The Relationship Between Body Image Disorders And Stress Levels In Cancer Patients Undergoing Chemotherapy At Banjarmasin Hospital - Yurida Olviani; Anita Karomah (Sean Institute, 2023)
Cancer is a non-communicable disease which is a public health problem. One of the procedures often used in cancer treatment is chemotherapy. Chemotherapy has physical and psychological side effects. The results of a preliminary study at Banjarmasin Hospital on 9 respondents and found that 5 of them often felt restless, anxious, and experienced baldness due to the effects of chemotherapy. To find out the relationship between body image disturbance and stress levels in cancer patients at Banjarmasin Hospital in 2019. This study used a quantitative method, cross sectional design. The sample consisted of 28 cancer patients undergoing chemotherapy at Banjarmasin Hospital, who were taken by porpusive sampling method. Data were analyzed using the Spearman rho test. The results showed that body image disturbance in cancer patients was moderate (64%) with a severe stress level category (43%). There is a significant correlation between body image disturbance and stress levels and the strength of the relationship is moderate.